Fostering Clinical Excellence Across an Academic Health System. Issue 8 (August 2016) - Tackett, Sean; Eisele, David; McGuire, Maura; Rotello, Leo; Wright, Scott
Abstract : Objectives: Changes in the US healthcare economic system are requiring academic health centers (AHCs) to restructure in pursuit of their traditional tripartite missions; engaging the individuals focused on clinical care is becoming more important. We conducted this study to guide our institution's transformation by identifying ways to formally recognize clinicians who are excelling in patient care and understand which forms of acknowledgment would be acceptable and motivating. Methods: A survey was developed by a large committee with representation spanning the AHC and was sent electronically in spring 2014 to stakeholders across the institution. Items assessed perceptions of the importance and present state of valuing clinical excellence, the utility of 14 potential metrics to assess clinical excellence, and the meaningfulness of seven potential rewards for clinical excellence. Bivariate and multivariate logistic regression models analyzed differences ( P < 0.05) by respondent sex, ethnicity, academic rank, primary clinical affiliation, and time spent in patient care and research activities. Results: A total of 1716 of 3168 (54%) stakeholders responded, including 1198 of 2151 (56%) individuals from academic hospitals, 114 of 276 (41%) from the outpatient affiliated practices, and 304 of 741 (54%) from satellite locations. Nearly everyone (96%) agreed that clinical accomplishments should be recognized, although a minority (47%) believed that clinicians were already valued. Most respondents selected 7 or more of 14 metrics as valid and reasonable for assessing clinical excellence. Popular metrics (eg, clinical productivity) were not believed to represent clinical excellence as much as others (eg, professionalism). Multivariate analysis found the least agreement among stakeholders on using published scholarship as evidence for clinical excellence, with the widest differences comparing senior faculty versus nonfaculty (88% vs 27%) and those with >75% of their time spent in patient care versus others (37% vs 73%). Most (six of seven) types of reward were perceived as meaningful by the majority of respondents, with little variation among subgroups across bivariate and multivariate analyses. Conclusions: This system-wide assessment was successful at identifying new strategies for recognizing clinical excellence. Other AHCs seeking institutional transformation may wish to perform a similar assessment. Abstract : The authors surveyed 1716 stakeholders across Johns Hopkins Medicine to identify ways to recognize and reward clinical excellence. The study identified new strategies for fostering clinical excellence and may provide a template for similar needs assessments in other academic health systems.